Aldo/keto reductase regulates L-lactate dehydrogenase activity as a key target for yogurt post-acidification - Qingqing Mu; Sitong Jia; Dongyao Li; Whenhao Zhao; Na Zhang; Miaoshu Wang; Hongtao Tian; Chen Li (Food Microbiology, 2026)

Selenomethionine antagonizes sodium arsenite-induced reproductive toxicity in zebrafish - Yan Zhang; Huan Wang; Xinru Bo; Yangfan Xu; Lingtian Xie; Yunyang Li; Jingli Mu; Jialing He; Na Zheng; Baoquan Zhao; Hongxing Chen; Wu Dong (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

A surface-engineered mycelial biofilm incorporating a self-cascading nanozyme for mycotoxin degradation in edible oils - Xue-ming Cao; Xue-ting Zhu; Yang-yang Geng; Ruo-mu Xia; Jin-min Zhang; Li-na Wu (Chemical Engineering Journal, 2026)

Scoparone alleviates cisplatin-induced acute kidney injury by inhibiting 5-lipoxygenase-mediated ferroptosis - Congcong Dai; Shuting Huang; Na Huang; Suwan Mu; Suwang Liu; Minhui Xie; Jing Mei; Yuhong Tang; Honghao Yu; Pengpeng Yue; Yong Li; Jun Ou (Toxicology and Applied Pharmacology, 2026)

CCT7 predicts poor prognosis and correlates with immune infiltration in colonic adenocarcinoma - Wenxu Li; Qizhong Shi; Yonghui Mu; Chenglei Li; Wenchao Zhao; Na Han (Journal of Molecular Histology, 2026)
CCT7, a member of the t-complex polypeptide 1 chaperone family, facilitates ATP-dependent protein folding; however, its role in development and progression of malignant tumors remains unclear. This study aimed to characterize the expression pattern of CCT7 in colonic adenocarcinoma (COAD) and evaluate its role in the initiation and development of COAD. Public bioinformatic databases were analyzed to assess CCT7 expression in COAD, and these findings were validated using human clinical specimens through immunohistochemistry (IHC) assay. The prognostic significance of CCT7 was examined using Kaplan–Meier method and Cox regression analysis. Gene Ontology-Biological Process (GO-BP) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses were performed to explore the potential biological functions and downstream pathways associated with CCT7. CCK-8, colony formation and Transwell assays were conducted to determine the impact of CCT7 on cell proliferation, migration and invasion in COAD cell lines. Associations between CCT7 expression and immune cell infiltration or drug sensitivity were evaluated using single-sample gene set enrichment analysis and correlation analysis. Finally, immune checkpoint inhibitor therapy scores and their relationship with CCT7 expression were assessed using data from The Cancer Immunome Atlas. CCT7 expression was significantly up-regulated statistically in COAD tissues compared with normal colonic tissues ( P < 0.05) and elevated CCT7 levels were associated with poorer prognosis of COAD patients ( P < 0.05). GO-BP enrichment analysis indicated that CCT7 was primarily involved in the processes related to cell proliferation and microtubule organization ( P < 0.05). Consistently, functional assays confirmed that CCT7 knockdown inhibited COAD cell proliferation, migration, and invasion ( P < 0.05). CCT7 expression showed a negative correlation with infiltration of most immune cell types ( P < 0.05) and demonstrated no significant association with predicted responses to PD-1 and CTLA-4 inhibitor therapies ( P > 0.05). Moreover, drug sensitivity analyses showed that CCT7 affected the sensitivity of COAD samples to several anti-cancer drugs ( P < 0.001). KEGG enrichment analysis revealed that CCT7 was associated with multiple pathways ( P < 0.05). CCT7 may function as an oncogenic driver that promotes the malignant phenotype of COAD and represents a promising prognostic biomarker. It may also provide a valuable reference for guiding clinical therapeutic strategies in COAD.

Mutant transcription factor CopR promotes LDB_RS05285 expression to suppress yogurt post-acidification and enhance texture stability - Wenhao Zhao; Xuemeng Fu; Dongyao Li; Qingqing Mu; Na Zhang; Yongsheng Sun; Miaoshu Wang; Hongtao Tian; Chen Li (Food Research International, 2026)

Comprehensive assessment of secondary metabolite diversity and in vitro anti-diabetic properties in Sanghuangporus quercicola cultured under different conditions - Mingxing Yu; Na Zhang; Xiaofeng Ma; Xiaoshuang Zhou; Shude Yang; Weihang Peng; Yin Li; Yuejun Mu; Xianhao Cheng; Rui Zhang; Yongfei Ming (Systems Microbiology and Biomanufacturing, 2026)

Microscopic probing into plasmodesmata (PD) and PD-derived intercellular gateways (PdIGs): Beyond morphology - Ming-fang Lv; Wei-na Shang; Yuan-xing Dai; Jun-ying Li; Yi Li; Shuai Fu; Jian Hong; Li Xie; Heng-Mu Zhang (Protoplasma, 2026)

Oxidative Stress-mediated Loss of Hippocampal Parvalbumin Interneurons Contributes to Memory Precision Decline After Acute Sleep Deprivation - Yu-zhu Gao; Kai Liu; Xin-miao Wu; Cui-na Shi; Qiu-li He; Hai-peng Wu; Jian-jun Yang; Hao Yao; Mu-huo Ji (Molecular Neurobiology, 2025)

AMPK activation by dietary acadesine improves fillet texture in large yellow croaker (Larimichthys crocea) fed a linseed oil-based diet - Shengdi Chen; Zihan Sun; Ningning Liu; Chenbin Yang; Na Li; Lu Li; Chaoqing Wei; Binlun Yan; Huan Gao; Peng Tan; Hua Mu (Aquaculture, 2025)

Microbiome changes and characteristics under nutrient injection for enhanced oil production at Daqing oilfield - Zi-Yue Fu; Wen-Tao Chen; Gui-Na Qi; Zhao-wei Hou; Yi-Fan Liu; Li-Bin Shou; Lei Zhou; Shi-Zhong Yang; Xiao-Lin Wu; Ji-Dong Gu; Bo-Zhong Mu (International Biodeterioration & Biodegradation, 2025)

Microplastic pollution in tropical coral reef ecosystems from the coastal South China Sea and their impacts on corals in situ - Weijie Bian; Yingxu Zeng; Yurui Li; Guangshui Na; Jun Mu; Shuguo Lv; Min Liu (Journal of Hazardous Materials, 2024)

Youth-derived Lactobacillus rhamnosus with prebiotic xylo-oligosaccharide exhibits anti-hyperlipidemic effects as a novel synbiotic - Luyao Dang; Dongyao Li; Qingqing Mu; Na Zhang; Chenwei Li; Miaoshu Wang; Hongtao Tian; Rajesh Jha; Chen Li (Food Research International, 2024)

Boosting solvent resistance and structure stability of degradable polyester through extended-chain crystal structure: A preliminary case of oil/water separation membrane - Jia-Yao Chen; Na Li; Siyang Wang; Tian-Yu Wu; Xiaoyu Meng; Hai-Mu Ye (Journal of Environmental Chemical Engineering, 2024)

Hexabromocyclododecane-induced reproductive toxicity in Brachionus plicatilis: Impacts and assessment - Na Lu; Yaya Zhang; Qinglin Mu; Yijun Li; Yuanyuan Li; Zhongyong Yan; You Wang (Aquatic Toxicology, 2024)

Characterization and fine mapping of a maize lesion mimic mutant (Les8) with enhanced resistance to Curvularia leaf spot and southern leaf blight - Jiankun Li; Tianyuan Fan; Ying Zhang; Ye Xing; Mengyao Chen; Ying Wang; Jie Gao; Na Zhang; Jinjun Tian; Chenyang Zhao; Sihan Zhen; Junjie Fu; et al. (Theoretical and Applied Genetics, 2024)

Nitrification-denitrification co-metabolism in an algal-bacterial aggregates system for simultaneous pyridine and nitrogen removal - Xiaoyu Zhang; Dan Chen; Xinying Hou; Na Jiang; Yan Li; Shijian Ge; Yang Mu; Jinyou Shen (Journal of Hazardous Materials, 2023)

The immunomodulatory effects of DNA-conjugated collagen scaffolds on bone healing - Jing-han Song; Jun-ting Gu; Gao-peng Dang; Zhi-ting Li; Chen Lei; Ling Li; Zhao Mu; Franklin R. Tay; Kai Jiao; Li-na Niu (Chemical Engineering Journal, 2023)

A new attempt to develop fermented milk with low whey protein allergenic potential using a top-down method - Ruiyang Ma; Na Miao; Qingyi Zhang; Shujuan Jiang; Xinling Li; Lei Chi; Yue Li; Guangqing Mu; Xuemei Zhu (Food Bioscience, 2023)

Organic geochemical characteristics and organic matter accumulation of the Eocene lacustrine source rock in the Yingxi area, Western Qaidam Basin, China - Fan Yi; Haisheng Yi; Chuanlong Mu; Wenqiang Tang; Na Li; Yun Chen; Kangzhi Tian; Yuxiang Shi; Jinxuan Wu; Guoqing Xia (International Journal of Earth Sciences, 2023)

External-loop split-type dynamic membrane photobioreactor for the treatment of high-strength pyridine wastewater: Improved photosynthetic oxygenation and mitigated membrane fouling - Xiaoyu Zhang; Na Jiang; Xinying Hou; Yan Li; Shijian Ge; Yang Mu; Jinyou Shen (Journal of Hazardous Materials, 2023)

Collagen-anchored cascade nanoreactors with prolonged intratumoral retention for combined cancer starvation and chemotherapy - Jingqing Mu; Yuyuan Du; Xingwei Li; Ran Yan; Haiping Zhong; Maoyu Cai; Na Yu; Jinchao Zhang; Xiaoyong Yuan; Xia Hua; Shutao Guo (Chemical Engineering Journal, 2023)

Human growth hormone proteoform pattern changes in pituitary adenomas: Potential biomarkers for 3P medical approaches - Biao Li; Xiaowei Wang; Chenguang Yang; Siqi Wen; Jiajia Li; Na Li; Ying Long; Yun Mu; Jianping Liu; Qin Liu; Xuejun Li; Dominic M. Desiderio; et al. (EPMA Journal, 2021)

Strategies for lead distribution in organs of Phragmites australis (Cav.) Trin. ex Steud. (Common reed) subjected to Pb pollution in flood and drought environments - Na Zhang; Jing Chen; Zhiqiang Li; Yujie Shi; Chunsheng Mu; Zhenhua Zhang (Hydrobiologia, 2018)

Alteration of cytochrome P450 1 regulation and HSP 70 level in brain of juvenile common carp (Cyprinus carpio) after chronic exposure to tributyltin - Zhi-Hua Li; Li-Qiao Zhong; Yan-Hua Wu; Wei-Na Mu (Fish Physiology and Biochemistry, 2016)

Transcriptome sequencing and analysis of sweet osmanthus (Osmanthus fragrans Lour.) - Hong Na Mu; Huo Gen Li; Liang Gui Wang; Xiu Lian Yang; Tao Ze Sun; Chen Xu (Genes & Genomics, 2014)

Genetic variation at 8q24, family history of cancer, and upper gastrointestinal cancers in a Chinese population - Heather P. Tarleton; Shen-Chih Chang; Sungshim Lani Park; Lin Cai; Baoguo Ding; Na He; Shehnaz K. Hussain; Qingwu Jiang; Li-Na Mu; Jianyu Rao; Hua Wang; Nai-Chieh Y. You; et al. (Familial Cancer, 2014)

Plants interactions between Suaeda salsa individuals are mediated by salinity stress - Hao Zhang; Jian-Na Li; Gen-Xuan Wang; Xin-Feng Dai; Mu-Qing Qiu; Ke-Feng Zheng (Acta Physiologiae Plantarum, 2007)

Methylenetetrahydrofolate reductase (MTHFR) C677T and A1298C polymorphisms and the risk of primary Hepatocellular Carcinoma (HCC) in a Chinese population - Li-Na Mu; Wei Cao; Zuo-Feng Zhang; Lin Cai; Qing-Wu Jiang; Nai-Chieh You; Binh Yang Goldstein; Guo-Rong Wei; Chuan-Wei Chen; Qing-Yi Lu; Xue-Fu Zhou; Bao-Guo Ding; et al. (Cancer Causes & Control, 2007)